The Therapeutic Alliance: Clients’ Categorization of Client-Identified Factors - Simpson, Arlene J.; Bedi, Robinder P. (Canadian Journal of Counselling and Psychotherapy, 2012)
Clients’ perspectives on the therapeutic alliance were examined using written descriptions of factors that clients believed to be helpful in developing a strong alliance. Fifty participants sorted previously collected statements into thematically similar piles and then gave each set of statements a title. Multivariate concept mapping statistical methods were used to obtain the most representative sort across participants. The resulting 14 categories (Emotional Support, Ability to Relate, Sharing the Counsellor’s Personal Experience, Good Boundaries, Interpersonal Demeanour, Body Language, Provided Resources and Homework, Availability, Planning and Approach, Directed Process Appropriately, Attentiveness, Approachable, Nonjudgemental, and Effective Listening ) provide a conceptual foundation useful for counsellor training and clinician development.